Patients’ Perception and Satisfaction on Model Pharmacies in Dhaka City, Bangladesh (Bangladesh Pharmaceutical Journal, 2018)
The aim of the present study is to find out the patients’ perception and satisfaction about model pharmacies in Dhaka city, Bangladesh. Model pharmacies of Dhanmondi, Mohammadpur, Mirpur, Kalabagan, Green road, Panthopath, Mohakhali, Gulshan and old Dhaka were considered as the study area. The factors for better health care service have been discussed from the points of patients’ perception. Pharmaceutical sector of Bangladesh is improving day by day although the inclusion of graduate pharmacists in the health sector is not yet implemented. Lack of modern facilities, improper management of medicines, selling of poor quality medicines as well as no counseling in pharmacies for the patients by “A grade” pharmacists are major causes of poor quality health care service. Recent initiation of model pharmacies in Bangladesh may be a hope for better healthcare management and patients’ satisfaction. The correlation matrix shows the factors that impact patients’ satisfaction and purchasing decision in model pharmacy. The most important and significant factors are counseling by “A grade” pharmacists, patient database system, affordable price and quality of medicines. Recommendations have been made for further improvement of the model pharmacies from the patients’ point of view and satisfaction, which might help to create a model for other developed and developing countries.Bangladesh Pharmaceutical Journal 21(1): 47-54, 2018